Isolated Facial Vein Thrombophlebitis Caused by Fusobacterium nucleatum: A Lemierre-Variant Case - Nicole Oska; Deni Peterson; Kendall Brothers; Ragamayi Maramraju; Asem Ayyad; Brianna Hohmann (Case Reports in Infectious Diseases)
Conclusion: This case emphasizes the importance of maintaining suspicion for Lemierre’s syndrome in patients with bacterial pharyngitis, especially when atypical symptoms such as facial pain occur. Although the internal jugular vein is most commonly affected, facial vein thrombosis may also occur. Early antibiotic treatment is critical for preventing severe complications including septic shock and embolization.